Remote assistance in physical therapy for normal-risk pregnant women (Research, Society and Development, 2023)
Physiotherapy applied to the Obstetrics plays an important role in the prevention and treatment of musculoskeletal, genitourinary, respiratory and vascular complaints.  In addition, it helps to prepare for childbirth and for a functional recovery after postpartum. The use of digital technologies has been strengthened in the Covid-19 pandemic, especially, in the gravid-puerperal context due to the high maternal and child health risk. The aim of this study was to evaluate the effect of a physical therapy protocol based on kinesiotherapy, in digital format, on somatic symptoms and the normal-risk pregnant women's level of satisfaction, as well as level of knowledgment. Case report, composed of 03 cases of pregnant women, from gestational week 13 to 30, with symptoms as back pain and cramps. Pregnant women were treated for 10 sessions, once a week, lasting 1 hour per session, between May and December 2022. Research ethics approval (CAAE: 47912421.6.0000.5323). All reported improvement in symptoms and high satisfaction levels. The level ok knowledge about Physiotherapy was low. This study demonstrated positive effects of a remote physiotherapeutic protocol to the pregnant`s health.